Protective effect of bosentan in experimental cerebral ischemia-reperfusion injury - Ataş, Eser; Özdemir, Hasan Hüseyin; Demir, Caner F.; Berilgen, M. Said; Kapan, Oktay; Akgün, Bekir; Kulo?lu, Tuncay (Turkish Society of Cerebrovascular Diseases, 2013)
OBJECTIVE: In cerebral ischemia, there are many factors that start the events leading to cell death. These factors contain free radical production, excitotoxicity, sodium and calcium flow disruption, enzymatic changes, stimulation of the inflamatuar process, the activation of platelets and leukocytes, delayed coagulation, endothelial dysfunction and endothelin (ET) release. Bosentan is the competitive antagonist of endothelin receptors; ETA and ETB. The aim of this study is to determine whether the protective effects of bosentan in experimental cerebral ischemia reperfusion injury. MATERIAL and METHODS: In this study, after ischemia-reperfusion procedure, bosentan molecule was regularly given to rats for 5 days. The brain tissues of decapitated rats were histopathologically examined. The levels of oxidant and antioxidant were determined in these brain tissues. RESULTS: It was observed that antioxidant levels and histopathological examinations were in rats given bosentan better than control group rats. CONCLUSION: In conclusion, this study has showed that bosentan may be an agent which could reduce negative effects resulting from neuronal death associated with ischemic stroke.
Deneysel serebral i?skemi?-reperfüzyon hasarinda bosentanin koruyucu etki?si?
Keywords: Bosentan; Ischemic stroke; Rat